Sensory Characterization Cocoa (Theobroma cacao L.) from Various Clones During Fermentation - Dwijatmoko, Muhammad Isa; Nurtama, Budi; Yuliana, Nancy Dewi; Misnawi, Misnawi (Green Engineering Society, 2025)
Indonesia is one of the biggest producers of cocoa bean. However, this big production of cocoa is not followed by its quality to fulfill chocolate industry requirement in flavor. Fermentation of cocoa is the most important process for producing high-quality flavor in cocoa beans. The goal of this study was to find out the fermentation effects of four clones on the sensory and chemical profile of cocoa liquor. Sensory analysis was conducted using a Quantitative Descriptive Analysis (QDA) method and the volatile components of the cocoa liquor were extracted using Solid Phase Microextraction (SPME) and then followed by identification using Gas Chromatography - Mass Spectrometry (GC-MS). Correlation between volatile components and sensory attributes were determined by OPLS (orthogonal partial least square) test. The results of this study indicate that OPLS S-plot GC-MS determination 2,3,5-trimethylpyrazine and acetic acid were found as the active compounds. Fermented and unfermented cocoa liquor from various cocoa clones had different sensory attributes. All cocoa clones of fermented cocoa beans were dominated by attributes of specific cocoa aroma, cocoa, and acidity, whereas in unfermented cocoa, they were dominated by astringent and bitter.